Monitoring of the Strength Development of Mortar and Concrete Based on the New Smart Piezoelectric Module - Qing Yang; Yaqin Zhang; Yuanping Wang; Jianxiu Hu; Jie Zhang (Advances in Civil Engineering)
To monitor the strength of mortar and concrete at different ages, this paper designs a novel smart piezoelectric module (SPM) based on traditional piezoelectric aggregates and embeds it into mortar specimens. By testing the strength development of mortar under different ages and water–cement (W/C) ratios, the relationship between pulse signal characteristic parameters and mortar age is obtained, and a predictive model for mortar strength is established. This method is then applied to monitor the hydration process of concrete at different ages. The study found that, during the strength development of mortar, a Hanning windowed five-peak pulse wave with a frequency of 100–120 kHz and a 5/7 wave crest was selected as the excitation signal, which could clearly distinguish P-wave and S-wave packets. The wave velocity curve changes with the specimen’s age, consistent with the trend of the mortar hydration curve, but the peak value of the received signal decreases in amplitude and occurs earlier with increasing mortar age. The change in the W/C ratio had a minimal effect on wave velocity, and the deviation of the established strength prediction model was within 10%, indicating good accuracy. The strength prediction model for concrete at different ages also showed a high degree of fit with a coefficient of determination of 97.54%.